Evaluasi Sistem Informasi Menggunakan Model HOT-FIT Pada Sistem Penerimaan Mahasiswa Baru di Lingkungan Universitas Muhammadiyah Gorontalo - Syahrial, Syahrial; Larote, Yonis; Lasarudin, Alter; Olii, Muhammad Ramdhan (Universitas Muhammadiyah Gorontalo, 2024)
This research was conducted to evaluate the website for new student admissions at the Universitas Muhammadiyah Gorontalo. Evaluation was carried out by applying the HOT-Fit model method to 4 components. Focus evaluation on technological, human, organizational and benefits components. The aim is to determine the level of usability of the Universitas Muhammadiyah Gorontalo New Student Admissions System. The research method was carried out quantitatively by collecting questionnaire data from the committee and registrants. The HOT-Fit model is applied in determining system evaluation indicators. The results of the HOT-Fit model approach on 8 variables are good. There is a test value for System Quality (KS) with a value of 73.8 (Good), then Service Quality (KL) with a value of 82.0 (Very Good), then Information Quality (KI) with a value of 72.3 (Good), then System Usage (PS) with a value of 77.9 (Good), then User Satisfaction (KP) with a value of 74.2 (Good), then Organizational Environment (LO) with a value of 82.7 (Very Good), then Organizational Structure (SO ) with a score of 66.7 (Good), and System Benefits (MS) with a score of 82.2 (Very Good). Categories in 8 variables are good to use based on the HOT-Fit method with a value obtained of 76.5. The Usability Testing results are good for use based on the HOT-Fit method and the assessment of new students as respondents.